Visual detection of Coxsackievirus A6 using a reverse transcription polymerase spiral reaction method - Wang, Kun; Ai, Yuanhang; Luo, Juan; Liang, Longying; Zhang, Weiwei; Cao, Guojun; Zha, He; Wu, Jie; Lei, Kun; Yao, Shifei; Wu, Kaifeng (Frontiers in Cellular and Infection Microbiology, 2025)
Coxsackievirus A6 (CVA6) ranks as a primary enterovirus associated with hand-foot-mouth disease (HFMD) and herpangina (HA). Given its significant role in these diseases, there is an urgent need for an efficient identification method. This study presents a novel visual approach based on the reverse transcription polymerase spiral reaction (RT-PSR) for the rapid detection of CVA6. We designed an RT-PSR assay that targets and amplifies a segment of the VP1 gene. Hydroxy naphthol blue (HNB) is incorporated as the detection agent in this assay. To evaluate the performance of the RT-PSR assay, we analyzed 142 clinical throat swab samples. The results were benchmarked against those obtained using quantitative reverse transcription - polymerase chain reaction (qRT - PCR). The RT-PSR assay operates at 65°C for 60 minutes and exhibits a detection limit of 10 copies/μL. When tested against other viruses, it consistently yielded negative results, demonstrating its high specificity. Moreover, the RT - PSR assay showed excellent agreement with a commercial qRT - PCR kit. In conclusion, by using HNB as an indicator, the RT - PSR assay emerges as a straightforward and highly sensitive method for detecting CVA6 in symptomatic throat samples. This approach holds great potential for improving the diagnosis and surveillance of CVA6 - related diseases.